Survey of vegetable species in urban arboreal flora and conflicts with public equipment in Macapá-Amapá (Research, Society and Development, 2022)
Macapá, the capital of the State of Amapá, has undergone a process of change of the territory with an increase in its expansion, with the development and creation of recent urban clusters, which were being created without the minimal urban infrastructure. However, the process of afforestation of several streets was borne by the Muniscipans, who were not guided by the public authorities on the choice of suitable arboreal species. This time, there is a need to know the diversity as well as the composition of arboreal species and the relationships with public apparatus. The present study aims to know and verify the status of the relations of public appliances and the urban afforestation, footwear situations and physical space of trees, power lines and internet in Macapá. The species survey was carried out by counting arboreal individuals with ≥ 5 cm in diameter at breast height (DAP) and ≥ 1.3 m in height existing in the arborization of public streets and logradouros of the Central neighborhoods, Jesus of Nazareth and Saint Inese. The confirmation of the trees was made through the help of the specialized botanical literature, analogies with materials deposited in the Herbarium of the Institute of Scientific and Technological Research of the State of Amapá (HAMAB) and through searches in the databases on the Internet. In the survey carried out in this work, in three central neighborhoods, 3434 individuals were counted, being 3076 individuals in the Central neighborhood, 265 individuals in the Jesus neighborhood of Nazareth and 93 individuals in the Santa Inês neighborhood. Of the 25 families catalogued, 12 families were selected that showed greater representativeness in the number of species with a higher frequency. Of these species, the most representative group, was Anacardiaceae in which presented 34% frequency of species specifically by Mangifera indicates L. with 1094 individuals (36.09%). The damage observed by the species was 53.8% that somehow has caused irregularities in the sidewalks as well as to the public roads. Electrical and logical wires have 85.58% compromised by vegetation. The urban forest present in the public roads of Macapá presents species of size that goes from medium to high size with a median found of 7.44 m among the trees inventoried in the sites analyzed. The Center neighborhood presented 73.84% while in Jesus of Nazareth with 90.39% of its individuals within the Classes (C, D and E), classes characterized by medium and high size. In the neighborhood Santa Inês presented 61.36% of its individuals within the smaller classes (A and B). A technical study is suggested to make the choice of species feasible, aiming at the operational and financial decrease so that the maintenance can be carried out in the afforestation of the city and the repairs in the infrarstructure of streets and collective accesses.